3D Printing of Mechanically Stable Calcium‐Free Alginate‐Based Scaffolds with Tunable Surface Charge to Enable Cell Adhesion and Facile Biofunctionalization. (9th January 2019) - Lin, Zifeng; Wu, Mingming; He, Huimin; Liang, Qingfei; Hu, Chengshen; Zeng, Zhiwen; Cheng, Delin; Wang, Guocheng; Chen, Dafu; Pan, Haobo; Ruan, Changshun
Abstract: For the 3D printing of bioscaffolds, the importance of a suitable bioink cannot be overemphasized. With excellent printability and biocompatibility, alginate (Alg) is one of the most used bioinks. However, its bioinert nature and insufficient mechanical stability, due to only crosslinking via cation interactions, hinder the practical application of Alg‐based bioinks in the individualized therapy of tissue defects. To overcome these drawbacks, for the first time, an ε‐polylysine (ε‐PL)‐modified Alg‐based bioink (Alg/ε‐PL) is produced. The introduction of ε‐PL improves the printability of the Alg‐based bioink due to increasing electrostatic interactions, which enhances the self‐supporting stability of the as‐printed scaffolds. The presence of the functional crosslinking –COOH and –NH2 groups in Alg and ε‐PL under mild conditions further enhances the mechanical stability of the scaffolds, far exceeding that of Alg/Ca 2+ scaffolds. The surface charge of the prepared scaffolds is finely tuned by the feed ratio of Alg to ε‐PL and postimmobilization of different quantities of additional ε‐PL, with a view to enhancing cell adhesion and further biofunctionalization. The results indicate that chondroitin sulfate, an extracellular matrix component, and vascular endothelial growth factor can be successfully applied to biofunctionalize the scaffolds via electrostatic adsorption for enhanced biological activity. Abstract : A mechanically stable alginate/ε‑polylysine (Alg/ε‑PL) scaffold is 3D printed to realize tunable surface charge which depends on the feed ratio of Alg to ε‑PL and the amount of post‑immobilized ε‑PL. An optimal design is defined for improving cell adhesion and biofunctionalization with the ultimate goal of enhancing the bioactivity of the Alg‑based scaffold.